Toponymy of Village Names in Lingga District Lingga Regency - Bima Ramadhan; Ahada Wahyusari; Dody Irawan (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This research aims to find and describe the toponymic aspects of village names in Lingga District, Lingga Regency. The object of this research is the name of the village in Lingga District, Lingga Regency which was obtained from informants. This research method is descriptive using a qualitative approach. The data collection techniques used were observation, recording, noting, interviews, and discourse transfer. The data analysis technique is carried out using recorded data obtained from interviews with informants, roughly transcribed in written language, then the data that has been roughly transcribed is then refined, the results of the refinement are adjusted again to the recording results, after the data transcript is perfected, the words and sentences those which are still unclear are given punctuation and other necessary marks, after the transcript is complete, typing is carried out, after obtaining data from the field, the information is transcribed perfectly, translated into Indonesian, and after the oral information is completed it is transcribed and translated perfectly into written language, analysis is carried out, after which the analysis is adjusted to the problem raised and the theory chosen. The results of data analysis obtained from the toponymy of village names in Lingga District, Lingga Regency, contain several aspects consisting of: Embodying aspects: water background, topographic background, and natural environmental background. Social aspects: social conditions and social status. Cultural Aspects: history.